PENGARUH PROFITABILITAS, PERTUMBUHAN PERUSAHAAN, GOOD CORPORATE GOVERNANCE DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Putri, Agnes Maidia; Friyani, Rita; Jumaili, Salman (Papanda Publisher, 2025)
This study aims to analyze the influence of profitability, company growth, good corporate governance (GCG), and corporate social responsibility (CSR) disclosure on firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) during the 2018–2023 period. Profitability is measured using net profit margin (NPM), company growth by total assets growth (TAG), GCG is proxied by institutional ownership, and CSR is assessed using the Global Reporting Initiative (GRI) 2021 standards. This study employs secondary data and purposive sampling, with a total of 21 companies over 6 years, resulting in 126 observations. Data analysis was conducted using SPSS version 26 with multiple linear regression. The results indicate that profitability (NPM) and GCG (institutional ownership) have a significant effect on firm value, while company growth (TAG) and CSR disclosure do not have a significant effect. These findings suggest that profit performance and sound corporate governance are key drivers in enhancing firm value within Indonesia’s energy sector.